2003
DOI: 10.1097/00024382-200303000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Enalaprilat Improves Systemic and Mesenteric Blood Flow During Resuscitation from Hemorrhagic Shock in Dogs

Abstract: We investigated the systemic and mesenteric cardiovascular effects of administering enalaprilat during resuscitation from hemorrhage. Dogs were hemorrhaged (mean arterial pressure [MAP] 40-45 mmHg for 30 min, then 30-35 mmHg for 30 min) and were then resuscitated with intermittent lactated Ringer's solution (200 mL/kg/h during first 40 min, and 60 mL/kg/h during the following 130 min, MAP 75-80 mmHg). A constant-rate infusion of saline with or without enalaprilat (0.02 mg/kg/h) was initiated after 40 min of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…However, all animals presented gradual cardiovascular deterioration without any significant difference between groups. These data contrast with findings of previous studies (24,29). During hypotensive resuscitation from hemorrhagic shock in dogs, enalaprilat infusion increased cardiac index, stroke volume index, superior mesenteric artery flow, stroke work, and left ventricular power output without causing a hypotensive crisis (29).…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…However, all animals presented gradual cardiovascular deterioration without any significant difference between groups. These data contrast with findings of previous studies (24,29). During hypotensive resuscitation from hemorrhagic shock in dogs, enalaprilat infusion increased cardiac index, stroke volume index, superior mesenteric artery flow, stroke work, and left ventricular power output without causing a hypotensive crisis (29).…”
Section: Discussioncontrasting
confidence: 88%
“…During hypotensive resuscitation from hemorrhagic shock in dogs, enalaprilat infusion increased cardiac index, stroke volume index, superior mesenteric artery flow, stroke work, and left ventricular power output without causing a hypotensive crisis (29). In other hemorrhage protocols applied to dogs, Wall et al (24) also showed that enalaprilat infusion during resuscitation was associated with an increase in systemic, celiac and portal blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Further details regarding the studies are available in Wall et al 20–22 The enalaprilat in each study was administered at 0.02 mg/kg/hr in a 0.9% saline vehicle. The 0.9% saline vehicle was administered at 2 mL/kg/hr whether or not it contained enalaprilat.…”
Section: Methodsmentioning
confidence: 99%
“…In the hopes of identifying such a site, investigators have evaluated the PCO 2 responses of many sites in both trauma and surgical patients [3][4][5][6][7][8][9][10] and hemorrhage and resuscitation laboratory studies. [11][12][13][14][15][16][17][18][19][20][21][22] In fact, the 'Endpoints of Resuscitation' clinical practice guidelines 23 provided on the Eastern Association for the Surgery of Trauma website (www.east.org/tpg.html) mention gastric intraluminal and other site PCO 2 in their 'Recommendations' sections regarding stratifying physiologic derangement and regarding improved patient outcomes and in their 'Scientific Foundation' section.…”
Section: Introductionmentioning
confidence: 99%